Heterodisomy in the GNAS locus is also a cause of pseudohypoparathyroidism type 1B (iPPSD3) - Africa Manero-Azua; Yerai Vado; Judith Gonzàlez Morlà; Eduard Mogas; Arrate Pereda; Guiomar Perez de Nanclares (Frontiers in Endocrinology)
ObjectiveTo identify the genetic cause underlying the methylation defect in a patient with clinical suspicion of PHP1B/iPPSD3.DesignImprinting is an epigenetic mechanism that allows the regulation of gene expression. The GNAS locus is one of the loci within the genome that is imprinted. When the methylation pattern is affected, it causes pseudohypoparathyroidism type 1B (PHP1B) or inactivating PTH/PTHrP signaling disorder 3 (iPPSD3). Paternal uniparental isodisomy (iUPDpat) of the chromosomal region comprising the GNAS locus has been described as one of the possible underlying genetic causes of the methylation alteration.MethodsWe present the case of a patient clinically diagnosed with iPPSD3. We performed a commercial methylation-specific multiplex ligation-dependent probe amplification (MS-MLPA), single-nucleotide polymorphism (SNP) array, and microsatellite study. In addition, we designed a custom MS-MLPA to analyze GNAS and nearby differentially methylated regions (DMRs).ResultsA methylation defect at the four GNAS-DMRs was detected, confirming the clinical diagnosis. Complementary techniques revealed the presence of a mixed isodisomy and heterodisomy of chromosome 20. Surprisingly, the GNAS locus was located on the heterodisomic zone.ConclusionsPaternal uniparental heterodisomy (hUPD) at the GNAS locus is also a genetic defect associated with iPPSD3. In the absence of parental samples, our custom MS-MLPA allows for the detection of a methylation defect at the GNAS locus and flanking DMRs, suggestive of uniparental disomy (UPD). We also suggest updating the actual guidelines to include hUPD at the GNAS locus as a cause of iPPSD3.